Inactivated ostreid herpesvirus-1 induces an innate immune response in the Pacific oyster, Crassostrea gigas, hemocytes - Lizenn Delisle; Anne Rolton; Julien Vignier (Frontiers in Immunology, 2023)
Infectious diseases are a major constraint to the expansion of shellfish production worldwide. Pacific oyster mortality syndrome (POMS), a polymicrobial disease triggered by the Ostreid herpesvirus-1 (OsHV-1), has devastated the global Pacific oyster (Crassostrea gigas) aquaculture industry. Recent ground-breaking research revealed that C. gigas possess an immune memory, capable of adaption, which improves the immune response upon a second exposure to a pathogen. This paradigm shift opens the door for developing ‘vaccines’ to improve shellfish survival during disease outbreaks. In the present study, we developed an in-vitro assay using hemocytes – the main effectors of the C. gigas immune system – collected from juvenile oysters susceptible to OsHV-1. The potency of multiple antigen preparations (e.g., chemically and physically inactivated OsHV-1, viral DNA, and protein extracts) to stimulate an immune response in hemocytes was evaluated using flow cytometry and droplet digital PCR to measure immune-related subcellular functions and gene expression, respectively. The immune response to the different antigens was benchmarked against that of hemocytes treated with Poly (I:C). We identified 10 antigen preparations capable of inducing immune stimulation in hemocytes (ROS production and positively expressed immune- related genes) after 1 h of exposure, without causing cytotoxicity. These findings are significant, as they evidence the potential for priming the innate immunity of oysters using viral antigens, which may enable cost-effective therapeutic treatment to mitigate OsHV-1/POMS. Further testing of these antigen preparations using an in-vivo infection model is essential to validate promising candidate pseudo-vaccines.